The reconstruction of tachyon inflationary potentials. Issue 8 (16th August 2017) - Fei, Qin; Gong, Yungui; Lin, Jiong; Yi, Zhu
Abstract: We derive a lower bound on the field excursion for the tachyon inflation, which is determined by the amplitude of the scalar perturbation and the number ofe e -folds before the end of inflation. Using the relation between the observables liken_s n s andr r with the slow-roll parameters, we reconstruct three classes of tachyon potentials. The model parameters are determined from the observations before the potentials are reconstructed, and the observations prefer the concave potential. We also discuss the constraints from the reheating phase preceding the radiation domination for the three classes of models by assuming the equation of state parameterw_{re} w re during reheating is a constant. Depending on the model parameters and the value ofw_{re} w re, the constraints onN_{re} N re andT_{re} T re are different. Asn_s n s increases, the allowed reheating epoch becomes longer forw_{re}=-1/3 w re =−1/3, 0 and1/6 1/6 while the allowed reheating epoch becomes shorter forw_{re}=2/3 w re =2/3 .